Rapid mass loss and disappearance of summer-accumulation type hanging glacier - Chun-Hai Xu; Zhong-Qin LI; Fei-Teng Wang; Pu-Yu Wang; Jian-Xin Mu (Advances in Climate Change Research, 2022)
Hanging glaciers hold the absolute dominant number in West China and their changes had important influences on local hydrology, sea-level rise and natural hazards (snow/ice avalanches). However, logistic and operational difficulties have resulted in the lack of in-situ-measured data, leaving us with poor knowledge of the changing behaviors of this type of glacier. Here, we presented the spatiotemporal pattern of seasonal and annual mass changes of a mid-latitude hanging glacier in the Tien Shan based on repeated terrestrial laser scanning (TLS) surveys during the period 2016–2018. The distributed glacier surface elevation changes exhibited highly spatiotemporal variability, and the winter elevation changes showed slight surface lowering at the upper elevations and weak thickening at the glacier terminus, which was contrary to altitudinal elevation changing patterns at the summer and annual scales. Mass balance processes of the hanging glacier mainly occurred during summer and the winter mass balance was nearly balanced (−0.10 ± 0.15 m w.e.). The glacier exhibited more rapid mass loss than adjacent other morphological glacier and the estimated response time of the glacier to climate change was very short (6–9 years), indicating hanging glaciers will experience rapid wastage and disappearance in the future even with climate change mitigation.